Cuenca Alta del Arroyo Malacara - Borras, Graciela; Auer, Alejandra Denise; Bruno, Mariana Paola (3º Taller Manejo sustentable de Tierras en el Sudeste Bonaerense: Los Pinos, 2024)
Presentación en diapositivas